Temporal trends in lower extremity amputation in Middle East and North Africa (MENA) region: analysis of the GBD dataset 1990-2019 - Yazan A. Al-Ajlouni; Mohamed Abouzid; Mohammad Tanashat; Ahmed Ahmed Basheer; Omar Al Ta'ani; Naciye Bilgin-Badur; Mohammad Islam (BMC, 2024)
Abstract Background Lower extremity amputations (LEAs) significantly contribute to mortality and morbidity, often resulting from peripheral artery disease and diabetes mellitus (DM). Traumatic injuries also account for many LEAs. Despite the global burden, the epidemiology of LEAs, particularly in the Middle East and North Africa (MENA) region, remains underexplored. This study utilizes the Global Burden of Disease (GBD) dataset to analyze temporal trends in LEAs in the MENA region from 1990 to 2019. Methods The study utilized the 2019 GBD dataset, which includes estimates for incidence, prevalence, and disability-adjusted life-years (DALYs) across 369 diseases. Age-standardized incidence rates (ASIRs) for LEAs were extracted for 21 MENA countries. Trends were analyzed using percentage change calculations and Joinpoint regression to identify significant shifts in LEA rates over time. Results From 1990 to 2019, male LEA rates generally decreased, while female rates increased. Significant increases in LEA rates were observed in Syria, Yemen, and Afghanistan, correlating with periods of conflict and instability. Conversely, countries like Iraq, Palestine, Sudan, Lebanon, Iran, and Kuwait saw marked decreases. The study highlighted a complex interplay of socio-political factors, natural disasters, and chronic diseases like DM in shaping LEA trends across the region. Conclusion The study reveals variable LEA trends in the MENA region, influenced by conflicts, natural disasters, and chronic diseases. These findings underscore the need for targeted public health interventions, improved healthcare access, and robust data collection systems to reduce the burden of LEAs and improve patient outcomes in the MENA region.